You are what you choose to eat: factors influencing young adults' food selection behaviour. Issue 4 (20th April 2015) - Hebden, L.; Chan, H. N.; Louie, J. C.; Rangan, A.; Allman‐Farinelli, M.
Abstract Background Young or 'emerging' adulthood (ages 18–24 years) is a life‐stage characterised by rapid weight gain, particularly among those born in recent decades, when environments have become saturated with cheap, highly palatable, processed foods. Although intervening in the immediate food environments of emerging adults is indicated, little is known about the factors influencing their food selection. The present study aimed to: (i) measure the relative importance of different influences on foods selected by emerging adults for consumption from a tertiary education setting and (ii) examine whether these influences differ according to gender, adiposity status, perceived stress and dieting or physical activity behaviours. Methods An online survey was administered with 112 emerging adults aged 19–24 years assessing demographics, perceived stress, dieting, physical activity and influences on food selection. Adiposity indicators (body mass index and waist circumference) were measured. Analyses compared the importance of influences on food selection by gender, adiposity, perceived stress, dieting and physical activity. Results Taste was the most important influence on food selection, followed by convenience (availability), cost, nutrition/health value, smell and stimulatory properties (alertness). Participants with an elevated waist circumference selected foods to help them cope with stress and control their weight. Those reporting a higher level of physical activity placed greater importance on nutritional/health value of foods but less importance on taste. Female dieters also placed less importance on taste and value for money. Conclusions Health promotion strategies addressing tertiary education food environments of emerging adults should ensure the ready availability of tasty and nutritious foods at a low cost.